Epicardial fat thickness and severity of coronary artery disease: a review - G., Vignesh; ., Tumbanatham (International Journal of Advances in Medicine, 2020)
People with diabetes are at high risk of coronary artery disease (CAD,) duration of diabetes is directly proportional to macro vascular complications. Epicardial fat through its various mechanism and anatomical closeness to the myocardium it has the direct impact on the severity of CAD. Aim of the study was to determine the correlation between epicardial fat thickness and severity of coronary artery disease in diabetic patients using syntax scoring system. The references used in this review were identified through PubMed and Google Schlor searches of articles published for the last 20 years. Search terms included CAD, correlation of EFT in CAD, syntax scoring system , Gensini scoring system, 2D-ECHO, diabetes in CAD. We reviewed 50 articles done on only humans. We reviewed relevant review articles also. It can be concluded that Epicardial fat thickness has significant correlation with severity of coronary artery disease.